2017
DOI: 10.1111/ajt.14272
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Cancer Screening Tests Among Recipients of Solid Organ Transplantation

Abstract: Population-based cancer screening recommendations are also suggested for solid organ transplant recipients (SOTR); however, recommendation adherence is unknown. In a population-based cohort of SOTR in Ontario between 1997 and 2010, we determined the uptake of breast, cervical, and colorectal cancer screening tests and identified factors associated with up-to-date screening using recurrent event analysis. We identified 4436 SOTR eligible for colorectal, 2252 for cervical, and 1551 for breast cancer screening. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…Modelling studies by Wong et al [ 219 , 220 ] suggest that screening for colon and cervical cancer would be cost effective in the kidney transplant population. In a population-based cohort of Ontario between 1997 and 2010, 77.5, 69.8 and 91.4% of eligible solid organ transplant recipients were not up to date with colorectal, cervical and breast cancer screening, respectively [ 221 ]. Solid organ transplant recipients with fewer co-morbidities, assessment by a primary care provider and continuity of care by a transplant specialist at a transplant centre were associated with higher rates of becoming screen up to date in this study [ 221 ].…”
Section: Screeningmentioning
confidence: 99%
“…Modelling studies by Wong et al [ 219 , 220 ] suggest that screening for colon and cervical cancer would be cost effective in the kidney transplant population. In a population-based cohort of Ontario between 1997 and 2010, 77.5, 69.8 and 91.4% of eligible solid organ transplant recipients were not up to date with colorectal, cervical and breast cancer screening, respectively [ 221 ]. Solid organ transplant recipients with fewer co-morbidities, assessment by a primary care provider and continuity of care by a transplant specialist at a transplant centre were associated with higher rates of becoming screen up to date in this study [ 221 ].…”
Section: Screeningmentioning
confidence: 99%
“…Likewise, 2 studies of kidney transplant recipients reported in Nordic countries reported 2-fold increases in cervical cancer risk among kidney transplant recipients, with no increase in uterine or ovarian cancers. 19 An Australian study of 166 lung transplant recipients reported an approximate 5-fold increase in low-and high-grade CIN incidence posttransplant when compared to a reference population. 6 The increase in this study of in situ (high-grade cervical intraepithelial neoplasia grade 3, CIN3) but not invasive cervical cancer may be explained by increased medical visits leading to earlier detection of noninvasive cervical lesions.…”
Section: Cervical Vulvar and Vaginal Cancersmentioning
confidence: 99%
“…However, a recent Canadian study of cervical cancer screening posttransplant showed lower adherence compared with the general population. 19 An Australian study of 166 lung transplant recipients reported an approximate 5-fold increase in low-and high-grade CIN incidence posttransplant when compared to a reference population. 20 The preponderance of evidence suggests that cervical cancer is increased and, therefore, cervical cancer screening remains a priority for SOT recipients, as discussed in more detail below.…”
Section: Cervical Vulvar and Vaginal Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection through screening has been shown to reduce cancer‐specific mortality in the general population. However, there is a lack of robust evidence regarding the benefits and harms, treatment effectiveness, and cancer‐related prognosis to support screening in the CKD population, with the uptake of cancer screening in patients with CKD remaining low …”
mentioning
confidence: 99%